1997
DOI: 10.1111/j.1460-9568.1997.tb01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the GABAA Receptor Inhibits the Proliferative Effects of bFGF in Cortical Progenitor Cells

Abstract: Recent studies have localized gamma-aminobutyric acid (GABA)-containing neurons and identified cells that express subunits of the GABAA receptor in the proliferative zone of the developing cerebral cortex and have demonstrated a role for GABA in cortical neurogenesis. We examined here the interactions between a number of neurotrophic factors, known to be involved in cortical cell proliferation and differentiation, and the GABAergic system (GABA and GABAA receptors) in the regulation of cell production in disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 37 publications
3
71
1
Order By: Relevance
“…Such factors include the amino acid neurotransmitters GABA and glutamate that reduce the number of VZ cells in S phase (L oT urco et al, 1995) and basic FGF (bFGF) that increases proliferation of neocortical precursors (Ghosh and Greenberg, 1995). A recent paper has demonstrated that GABA can counter the proliferative effects of bFGF, suggesting an interaction between these distinct signaling systems (Antonopoulos et al, 1997).…”
Section: Abstract: Neurogenesis; Cerebral Cortex; Development; Gap Jmentioning
confidence: 99%
See 1 more Smart Citation
“…Such factors include the amino acid neurotransmitters GABA and glutamate that reduce the number of VZ cells in S phase (L oT urco et al, 1995) and basic FGF (bFGF) that increases proliferation of neocortical precursors (Ghosh and Greenberg, 1995). A recent paper has demonstrated that GABA can counter the proliferative effects of bFGF, suggesting an interaction between these distinct signaling systems (Antonopoulos et al, 1997).…”
Section: Abstract: Neurogenesis; Cerebral Cortex; Development; Gap Jmentioning
confidence: 99%
“…Such factors include the amino acid neurotransmitters GABA and glutamate that reduce the number of VZ cells in S phase (L oT urco et al, 1995) and basic FGF (bFGF) that increases proliferation of neocortical precursors (Ghosh and Greenberg, 1995). A recent paper has demonstrated that GABA can counter the proliferative effects of bFGF, suggesting an interaction between these distinct signaling systems (Antonopoulos et al, 1997).In addition to interacting with extracellular diffusible factors, cells within the VZ can interact directly with each other by intercellular coupling (LoTurco and Kriegstein, 1991). The function of cell coupling in the VZ is not known; however, gap junction communication among cells has been shown to be an important regulator of development in other systems (Guthrie and Gilula, 1989).…”
mentioning
confidence: 99%
“…The neurotransmitters GABA and glutamate are shown to reduce the number of proliferating cells in dissociated or organotypic cultures of rat neocortex (19). GABA partially blocks the bFGFinduced increase in cell proliferation (20), but promotes cell proliferation in cultures of rat cerebellar progenitors (21). Signals mediated by ionotropic GABA A R are shown to promote neuronal differentiation after depolarization in neural progenitors of adult mouse hippocampal slices (22).…”
Section: Introductionmentioning
confidence: 99%
“…T he production of new neurons, or neurogenesis, is controlled in part by locally secreted factors that regulate proliferation (1)(2)(3)(4)(5). Ligands for G protein-coupled receptors (GPCR) may play significant roles in neurogenesis in a regionally or developmentally specific fashion (6)(7)(8)(9).…”
mentioning
confidence: 99%